2019
DOI: 10.1016/j.scitotenv.2018.09.231
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the global hydrological droughts of 2003–2016 and their relationships with teleconnections

Abstract: Droughts often evolve gradually and cover large areas, and therefore, affect many people and activities. This motivates developing techniques to integrate different satellite observations, to cover large areas, and understand spatial and temporal variability of droughts. In this study, we apply probabilistic techniques to generate satellite derived meteorological, hydrological, and hydro-meteorological drought indices for the world's 156 major river basins covering 2003-2016. The data includes Terrestrial Wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(62 citation statements)
references
References 91 publications
(84 reference statements)
4
58
0
Order By: Relevance
“…The results show that: (1) the annual runoff sequence of KRB changed significantly after 1979, which was consistent with the introduction of large-scale coal mining; (2) under the same drought recurrence period, the drought duration and severity in the human activity stage were significantly worse than in the natural and simulation stages, indicating that human activities changed the drought risk in this area; and (3) human activities had little impact on drought severity in the short duration and low recurrence period, but had a greater impact in the long duration and high recurrence period. These results provide scientific guidance for the management, prevention, and resistance of drought; and guarantee sustainable economic and social development in the KRB.On analyzing several research works, we found that drought is affected by climatic factors (natural climate and anthropogenic climate), environmental resource factors, topographic and geomorphic factors, water resource conditions, social and economic factors, population growth factors, coal mining, water conservancy facilities, and other land use factors [7,[9][10][11][12][13]. Strzepek et al [14] and Kirono et al [15] used global climate models to study the factors affecting drought in Australia and most parts of the United States, respectively.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The results show that: (1) the annual runoff sequence of KRB changed significantly after 1979, which was consistent with the introduction of large-scale coal mining; (2) under the same drought recurrence period, the drought duration and severity in the human activity stage were significantly worse than in the natural and simulation stages, indicating that human activities changed the drought risk in this area; and (3) human activities had little impact on drought severity in the short duration and low recurrence period, but had a greater impact in the long duration and high recurrence period. These results provide scientific guidance for the management, prevention, and resistance of drought; and guarantee sustainable economic and social development in the KRB.On analyzing several research works, we found that drought is affected by climatic factors (natural climate and anthropogenic climate), environmental resource factors, topographic and geomorphic factors, water resource conditions, social and economic factors, population growth factors, coal mining, water conservancy facilities, and other land use factors [7,[9][10][11][12][13]. Strzepek et al [14] and Kirono et al [15] used global climate models to study the factors affecting drought in Australia and most parts of the United States, respectively.…”
mentioning
confidence: 76%
“…On analyzing several research works, we found that drought is affected by climatic factors (natural climate and anthropogenic climate), environmental resource factors, topographic and geomorphic factors, water resource conditions, social and economic factors, population growth factors, coal mining, water conservancy facilities, and other land use factors [7,[9][10][11][12][13]. Strzepek et al [14] and Kirono et al [15] used global climate models to study the factors affecting drought in Australia and most parts of the United States, respectively.…”
mentioning
confidence: 99%
“…As altimetry data alone only contain limited information on the river flow volumes, we first identified and discarded solutions that were least likely to preserve observed the seasonal water storage (S tot ) fluctuations. To do so, the monthly modelled total water storage ( tot,mod = i + u + f + s ) relative to the 2004-2009 timemean baseline in each grid cell was compared to water storage anomalies as obtained from the GRACE data product (Tang et al, 2017;Fang et al, 2016;Forootan et al, 2019;Khaki and Awange, 2019). In the GRACE 300 product, the same time period was used for the time-mean baseline (Swenson and Wahr, 2006;Swenson, 2012;Landerer and Swenson, 2012).…”
Section: Parameter Selection and Model Performance Based On The Seasomentioning
confidence: 99%
“…In long-term analyses of annual water balance, the variation in terrestrial total water storage (TWS), which includes snow, ice, plant water, surface water, soil moisture and groundwater, is usually considered insignificant. However, at subannual timescales, TWS plays a critical role in the partitioning of precipitation into runoff and evapotranspiration (Milly, 1994;Reager et al, 2014;Forootan et al, 2019). For example, an elevation in the water table level can increase the fractional saturated areas, where surface runoff predominates over infiltration, and increase the vegetation access to water table directly by deeper roots or indirectly by capillary suction or water redistribution.…”
Section: Introductionmentioning
confidence: 99%